التفسير الصوفي الأشاري :دراسة نقدية ومقارنة بين روح البيان للبروسوي والبحر المديد لابن عجيبة - Mahyuddin Bin Hashim (Universiti Sains Islam Malaysia, 2024)
This research aims to define Tafsir Sufi Ishari, Tafsir Ruhul Bayan by Al-Burusawi (1715) and Tafsir Al-Bahr Al-Madid by Ibn Ajibah (1809). The research as well will extrapolate Tafsir Sufi Ishari for Quranic verses in the two books which related to the issues of the Madarij al-Salikin (scales of seekers) in Sufism, methods of practice, heart purification and profits of mysticism. The methodology for this research in analyzing information depends on the descriptive approach, and on collecting all facts and information. It also uses the analytical and criticism approach by matching the scholarly conditions of acceptance regarding Tafsir Sufi Ishari with what was interpreted by Al-Burusawi and Ibn Al-Ajibah. Then compare, evaluate and criticize them. Therefore, The findings indicate that the Tafsir Sufi Ishari – which is One of the types of the Quranic exegesis based on interpretations of verses contrast the classical comentaries - by Al-Burusawi and Ibn Ajibah that matching the conditions were based on two foundations. Firstly: The Tafsir Sufi Ishari was interpreted accordingly to general verses' meaning and exegesis. Secondly: The relationship between Tafsir Sufi Ishari to al-Ma'thur is like the relationship between cause and effect. The study also revealed that the contradictions with conditions in Tafsir Sufi Ishari are based on three foundations. Firstly: The interpretations of Burusawi and Ibn Ajibah were so far from the common use of Arabic understanding. Secondly: The interpretations made were analogous compared to other normal exegesis. Thirdly: to generalize some issues which are strictly individuals. In fact, if Burusawi and Ibn Ajibah limited their interpretation to their Ishari views there is no differences between them and the doctrine of Shiites Batiniyyah!, But our trust in their scholarly Tafsir, their confirmation of classical interpretation and their condemnation of Batiniyyah understanding make their Tafsir Ishari valid and well concerned.